MEMAKSIMALKAN KEMAMPUAN MENELUSUR PADA PORTAL E-RESOURCES PERPUSTAKAAN NASIONAL RI - Hanum, Atiqa Nur Latifa (Universitas Tanjungpura, 2019)
Abstract Searching for information can be done simply (basic) or complex. Its depends on the level of ability of the information seeker. The study was to describe the relationship between the ability to search and the relevance of search results on the e-resources portal of the National Library of Indonesia (PNRI) so that it can find ways to maximize the ability to search for scientific digital information sources on that portal. The method used was quantitative with descriptive statistics analysis. The technique of colleting data was questionnaires, interviews, and literature studies. For the population, there were 108 active students of D-3 Library Science Study Program in the FKIP, while the sample was D-3 Library Science Study Program students who have accessed e-resources services of PNRI with the numbers 45 students who are considered representative in terms of search capabilities. The results showed that there was a relationship between the ability of students in searching and e-resources database of PNRI with the relevance of search results. It can be seen from the suitability of journal articles and electronic books that they were searching. 78,05% of students were able to search and got relevant results because they were influenced by the selection strategy of the search strategy. The effectiveness of strategy selection was also influenced by the ability to break down or formulate keywords. In these study, the ability to formulate keywords as the basis of search was in the low category, but the combination to get the needed information was in the high category. Keywords: searching for information, e-resources, National Library of Indonesia